RUSSIA, THE WEST, AND THE SCO COUNTRIES IN THE CENTRAL EURASIA ENERGY PROJECTS - MOROZOV, Yuri (CENTRAL ASIA AND THE CAUCASUS, 2008)
In the near future energy will remain a geopolitical category. This is especially true of the oil and gas sphere. Indeed, according to the International Energy Agency (IEA), organic fuels will remain the main energy source until 2030 in the world, where the developed countries consume the greater part of the oil and gas produced. In 2006, the United States, which consumes 24.6 percent of the world oil production, imported 60.2 percent of its domestic consumption. The EU members, which in 2006 imported about 80 percent of the oil they consume, depend on oil to a much greater extent.1 Russia is a unique country in this respect: its proven oil and gas resources are estimated at 74.4 billion barrels (6.2 percent of the world’s total), which makes it the seventh oil-rich country in the world; it comes second after Saudi Arabia as an oil exporter.The Energy Strategy of Russia until the Year 2020, which envisages that “the role of any country on the world’s energy market determines, to a great extent, its geopolitical influence” showed a clear understanding of the importance of energy as a geopolitical factor.2 Today, the European Union is the main exporter of Russia’s Soviet inheritance, which makes it dependent on European exports— 86 percent of the exported oil and 92 percent of the exported gas. This explains why the Energy Strategy insisted on diversified exports—to the APR and South Asia, the two regions with the world’s highest growth rates, which have already changed the structure of the world’s oil demand. The APR’s share in Russia’s oil export should increase from the present 3 to 30 percent in 2020, while gas exports are expected to rise to 15 percent. The Strategy describes China, Japan, South Korea, and India as the most promising partners On the other hand, the European Union is aware of its great dependence on Russia’s exports: 28 percent of oil and 40 percent of gas. In the last 35 years the share of Asian gas in Russia’s oil export to Europe became fairly noticeable in the overall volume of the world’s oil trade: back in 1970 the Soviet oil pipelines moved 46 billion cu m; in 1990, this volume rose 7-fold; and in 2004, twice as much again (680 billion cu m). The transit disagreements with Ukraine in January 2006 and Belarus in January 2007 forced the EU to concentrate on diversifying its gas exports to diminish its dependence on Moscow.